PENGARUH STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP PEMBELIAN TIDAK TERENCANA (IMPULSE BUYING) pada MATAHARI DEPARTEMENT STORE PLAZA SIMPANG LIMA SEMARANG - Putri, Cintia Maharani; Prihatini, Apriatni Endang; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2015)
Modern retail that increasingly cause competition amongst the modern retail. In addition, the rise of modern retail also allows consumers to choose the preferred retail and matched with consumer desires. That matter, which requires the owners of retail outlets to continue to pay attention to the stores in order to survive in competition fairly tight retail businesses and to encourage an increase in profits. Increased profits can be done by increasing the purchase, and spontan purchase became an effective way. Unplanned purchases can be influenced by store atmosphere and convenient service. Matahari Department Store Plaza Semarang Simpang Lima as a retail company, continue to create the store's atmosphere and better service quality, in order to continue to survive in the competitive retail businesses are quite strict. Which is expected to influence consumers to buy products at the store mainly unplanned purchases.This study aimed to examine the effect of store atmosphere and quality of service to unplanned purchase (impulse buying). This type of research is explanatory research. The sampling technique used purposive sampling technique. Respondents in this research were 100 respondents who shopped at the Matahari Department Store Plaza Semarang Simpang Lima. Researchers at the data analysis using SPSS for windows 16.0.Results of this study concluded that the store atmosphere has a positive and significant impact on impulse buying, quality of service has a positive and significant impact on impulse buying, and store atmosphere and quality of service has a positive and significant impact on impulse buying. Results of this study suggest that in order to increase the purchasing behavior of unplanned need to take into account the store atmosphere and quality of service.